Report of the Hospital Sub-committee - Horder, Thomas, 1871-1955 (London : Institutional Management Association)
1943-09-11 1943 1940s 15 pages Subjects:— Proportional allocation of time. Cookery 51% Book-keeping and Business Affairs 14% Needlework, Upholstery and Soft-Furnishing 7% Laundry-work 7% Housewifery 7% Nutrition 6% Chemistry, Hygiene, Physiology, First-Aid and Home Nursing 5% English 2% Fuels - Equipment and Appliances in relation to Cooking, Heating and Lighting 1% It was unanimously agreed that for those training to become Domestic Administrators, too much time in the present courses is devoted to needlework, and much more time is needed for book-keeping and business affairs. 7. In the third year of training lectures on institutional management should be given, six months of the time should be spent in gaining experience in different types of institutions and six months in the particular type of institution in which the students wish to work ultimately. 8. While gaining practical experience the students should not be supernumerary but should be responsible for part of the normal work of the institution. 9. Following on this practical experience reports on the students' work should be made by the institution where they have been working. The report should be made on a form asking for information on:— i. Orderliness and method. ii. Powers of observation. iii. Adaptability and staying-power. iv. Handling of staff. v. Personality and capability. vi. Office experience. vii. General standard of work. viii. Any special observation. 10. The students' work during this period should include:-- (a) Administration. Instruction in:— i. The organisation of the work of each department. ii. The management of staff and employer's liabilities. iii. Repairs and renewals in each department. 4 292/842/2/104